(3GdeYjGQ GdeYQH hGdLGeY GdeZQH Yf aJGhi YdeGA EaQjbjI hGdCfOdS hGdeZQHs - (3CHh GdYHGS CMeO Hf jMji Hf eMeO Hf YHO GdhGMO Hf Ydj GdhfTQjSj,J (B914 (3g` s ((3GdQhVI GdTQjaI (B_ (3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3GdMeO ddg GdeJaVd HELGHI GdSGFd hHYO agPG cJGH SejJg GdeYjGQ GdeZQH Yf aJGhi hQJHJg Ydi GdCHhGH GdabgjI hUQMJ HCSeGA GdeaJjf fhGRd GdWgGQI SFd SjOi Gdabjg s
(3BNQgG (B:s
(3hSFd SjOi Ydi Hf eMShO Yf WYGe GdYbjbg GdPi PcQg eGdc aCLGH hcPdc eGdGjLRi ajgG hGddg CYde fLR s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM HGdCShO GdSejcs
(3fSNI eUMMI s
(3ajgG fhGRd GdWgGQI hGdUdGI hGdLfGFR hGdRcGI hGdUjGe hGdML hGdUjO hGdPHGFM hGdGTQHI hGdCVMjI s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdESdGejs